Influence of Hypertension, Alone and in Combination with Other Vascular Risk Factors on Cognition - R. Czuriga-Kovács, Katalin; Czuriga, Dániel; Csiba, László (CNS & Neurological Disorders - Drug Targets, 2016)
Hypertension is one of the most important modifiable risk factors of cardioand cerebrovascular diseases, responsible for the development of severe target organ damages. It has been shown that hypertension is associated with an increased prevalence of cognitive decline. It negatively affects the cognitive battery and accelerates dementia. Beside the known detrimental effects of senile hypertension on cognitive performance in the elderly population, previous studies pointed out that young, hypertensive individuals may also suffer from hypertension related changes in their cognitive capacity. Given the high prevalence of hypertension in a wide range of the age pyramid (young individuals, middle aged adults, elderly people), specific cognitive deficits may be present in a large portion of the population putting a heavy burden on society. Better understanding of the underlying mechanisms of hypertension induced cognitive impairment may contribute to the identification of its initiating pathophysiological factors, and serve an earlier diagnosis, intervention at an early stage and prevention of further deficits. Our aim with the current review was to summarize some of the previous findings regarding altered cognitive performance of individuals with hypertension and of those with the most common co-existing risk factors. Furthermore, efforts to explore effects of various antihypertensive medications on cognition and to survey proposed pathophysiological mechanisms of hypertension induced cognitive changes have been made.
Keywords: vascular risk factors